Role of Environmental Factors in Legume-Rhizobium Symbiosis: A Review - Liudmyla Yeremko; Katarzyna Czopek; Mariola Staniak; Mykola Marenych; Volodymyr Hanhur (Biomolecules)
Legumes play a pivotal role in addressing global challenges of food and nutrition security by offering a sustainable source of protein and bioactive compounds. The capacity of legumes to establish symbiotic relationships with rhizobia bacteria enables biological nitrogen fixation (BNF), reducing the dependence on chemical fertilizers while enhancing soil health. However, the efficiency of this symbiosis is significantly influenced by environmental factors, such as soil acidity, salinity, temperature, moisture content, light intensity, and nutrient availability. These factors affect key processes, including rhizobia survival, nodule formation, and nitrogenase activity, ultimately determining the growth and productivity of legumes. This review summarizes current knowledge on legume-rhizobia interactions under varying abiotic conditions. It highlights the impact of salinity and acidity in limiting nodule development, soil temperature in regulating microbial community dynamics, and moisture availability in modulating metabolic and hormonal responses during drought and waterlogging. Moreover, the role of essential nutrients, including nitrogen, phosphorus, potassium, and trace elements such as iron, molybdenum, and boron, in optimizing symbiosis is critically analyzed.